MoneyMind: Web-Based Financial Management to Manage and Save Money - Andika Isma; Della Fadhilatunisa; sa Diarra; Soussou Raharimalala; Andi Shelma Putri Azzahra; Putri Nanda Sari (Program Studi Teknik Komputer, 2023)
MoneyMind is a web-based financial management platform designed to assist individuals in managing and saving money effectively. This research aims to develop and test the MoneyMind system using research methods of data collection, system analysis, system development, and system testing. The data is analyzed to identify user needs, challenges faced in financial management, as well as features and functions expected from MoneyMind. Based on the results of the analysis, the MoneyMind system was developed using a web-based software development approach. Programming and web design are used to create intuitive and functional user interfaces. After development, the MoneyMind system was tested using the black box system testing method. Testing is done to ensure that all features work properly, user data can be stored securely, and the user interface works smoothly. The test results show that MoneyMind can provide an effective solution in managing personal finances and help users save money. The intuitive user interface and features allow users to track their income and expenses, set budgets, monitor financial goals, and analyze spending patterns with ease. This research shows that MoneyMind as a web-based financial management platform can provide significant benefits to individuals in managing and saving money.